2005
DOI: 10.1111/j.1744-7429.2005.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation and Succession of Arthropod Communities in Inflorescences and Infructescences of Xanthosoma (Araceae)1

Abstract: Phytotelmata, small aquatic ecosystems within different structures of terrestrial plants, occur in the inflorescescences and infructescences of Xanthosoma (Araceae). This study reports changes in composition and abundance of arthropods during the anthesis of inflorescences and in the developing infructescences of three species of Xanthosoma at three different geographic locations: (1) X. undipes in a tropical cloud forest of Costa Rica, Central America; (2) X. daguense in a tropical cloud forest in the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…As the number of bracts increased in the inflorescences, abundance and richness also tended to increase. This change in the colonizing fauna has been reported previously (Seifert 1982;Richardson & Hull 2000;Garcia-Robledo et al 2005;Yee & Willig 2007) and recently, Benítez-Malvido et al (2016) have shown the influence of the fragmentation of the tropical forest on the phytotelmata arthropod biodiversity in Heliconia bracts. The habitat affects species abundance, and the diversity and composition were higher in continuous forest (Benítez-Malvido et al 2016).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As the number of bracts increased in the inflorescences, abundance and richness also tended to increase. This change in the colonizing fauna has been reported previously (Seifert 1982;Richardson & Hull 2000;Garcia-Robledo et al 2005;Yee & Willig 2007) and recently, Benítez-Malvido et al (2016) have shown the influence of the fragmentation of the tropical forest on the phytotelmata arthropod biodiversity in Heliconia bracts. The habitat affects species abundance, and the diversity and composition were higher in continuous forest (Benítez-Malvido et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…In South America, nitidulids were reported in the bromeliad Aechmea distichantha Lem. (Bromeliaceae) in Argentina (Montero et al 2010), and in inflorescences of Xanthosoma Schott (Araceae) in Costa Rica (Garcia-Robledo et al 2005). In southeastern Brazil, nitidulids are associated with the bromeliad Vriesea inflata Wawra (Bromeliaceae) in fragments of the Atlantic Forest (Mestre et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Bromeliads have a comparatively small geographic range, with some variation in trophic structure (Srivastava et al. , 2008), but the biogeography of bromeliad food webs has not been well studied (García‐Robledo et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…130 genera/3300 species, the Araceae are a speciose family of monocot angiosperms with a mostly tropical distribution and enormously varied pollination strategies. Pollination is achieved by many different kinds of insects (e.g., flies, beetles, bees), with large cyclocephaline scarab beetles (Coleoptera: Scarabaeidae: Dynastidae) playing a significant role in Neotropical genera, such as Dieffenbachia , Philodendron , and Xanthosoma (e.g., Garcia-Robledo et al 2005 ; Gibernau et al 1999 ; Young 1986 ). These scarab beetles arrive at night, attracted by intense floral scents (with emission supported by thermogenesis), use the inflorescences as feeding and mating sites, and effect pollination by their activities (e.g., Pereira et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%